2019
DOI: 10.1101/752691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimensionality changes actin network through lamin A and C and zyxin

Abstract: The actin cytoskeleton plays a key role in differentiation of human mesenchymal stromal cells (hMSCs), but its regulation in 3D tissue engineered scaffolds remains poorly studied. hMSCs cultured on 3D electrospun scaffolds made of a stiff material do not form actin stress fibers, contrary to hMSCs on 2D films of the same material. On 3D electrospun-and 3D additive manufactured scaffolds, hMSCs also displayed fewer focal adhesions, lower lamin A and C expression and less YAP1 nuclear localization. Together, thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…[14][15][16][17] We have previously shown that hMSCs in 3D electrospun (ESP) scaffolds have fewer stress fibers and focal adhesions than in 2D. 35,36 We have also seen that 3D alginate hydrogels show the same trend, in line with results published by others. [37][38][39][40][41][42][43][44][45] Indeed, when stained for zyxin, hMSCs cultured in 3D RGD-modified alginate hydrogels or 3D ESP scaffolds displayed very few zyxin positive focal adhesions, while many large focal adhesions were observed in 2D TCP ( Figure 4A).…”
Section: Increased Stc1 Secretion In 3d Culturessupporting
confidence: 88%
See 1 more Smart Citation
“…[14][15][16][17] We have previously shown that hMSCs in 3D electrospun (ESP) scaffolds have fewer stress fibers and focal adhesions than in 2D. 35,36 We have also seen that 3D alginate hydrogels show the same trend, in line with results published by others. [37][38][39][40][41][42][43][44][45] Indeed, when stained for zyxin, hMSCs cultured in 3D RGD-modified alginate hydrogels or 3D ESP scaffolds displayed very few zyxin positive focal adhesions, while many large focal adhesions were observed in 2D TCP ( Figure 4A).…”
Section: Increased Stc1 Secretion In 3d Culturessupporting
confidence: 88%
“…A reduced number of focal adhesions and actin stress fibers have been previously reported in a number of studies in both hydrogels [37][38][39][40][41][42][43][44][45] and ESP scaffolds. 35,36 The increase of STC1 in 3D cultures has been shown before in different 3D culture systems. [14][15][16][17] Our data suggest that this might be due to a reduction in focal adhesions and/or actin-myosin tension.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, the optimal stiffness for differentiation and proliferation defer per cell type [56,57] . We have previously shown that hMSCs experience the ESP scaffolds used here as a soft substrate, demonstrated by fewer focal adhesions, less lamin A/C and less YAP nuclear translocation [58] . The difference in focal adhesion formation between hMSCs and fibroblasts observed here potentially derives from a different response to matrix stiffness.…”
Section: Discussionmentioning
confidence: 90%
“…While actin-myosin inhibition by blebbistatin did decrease FGFR1 expression, zyxin knockdown did not. Although fewer than normally, zyxin knockdown cells still form focal adhesions 25,40 . Our data suggests that the actin-myosin tension between these focal adhesions is still sufficient to maintain a higher FGFR1 expression, as full inhibition of actin-myosin by blebbistatin reduced FGFR1.…”
Section: Discussionmentioning
confidence: 94%
“…As transplanted cells for regenerative medicine inevitably end up in a 3D environment, we wanted to investigate the potential mechanosensitive regulation of FGFR1 and response to bFGF in 3D. Previously, we have shown that hMSCs reduce cellular tension in 3D microfibrillar substrates and other 3D environments 25 . Thus, to investigate the effect of bFGF in 3D and to potentially find leads on FGFR1 regulation, we started by investigating the response of hMSCs to bFGF in a 3D microfibrillar environment.…”
mentioning
confidence: 99%